NILAI-NILAI PERSONALITAS ENTREPRENEURSHIP DAN PRODUKTIVITAS USAHA MIKRO RUMPUT LAUT - Hasmiah Herawaty (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2020)
This research identifies the personality values of entrepreneurship consisting of dicipline, honesty, creativity, innovation, and independence and test those effect on the productivity of seaweed entrepreneur of micro scale. This research was conducted in Lasitae Village, Pancana Village of Tanete Sub-district with 66 respondents. The data were analyzed using multiple regression. The result of this research pointed out personality values consisting of discipline, honesty, creativity, innovation, and independence affect the productivity of seaweed entrepreneur.